2022
DOI: 10.1002/batt.202200308
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Pure Inorganic Electrolyte for Aqueous Sodium‐Ion Batteries Operating at −60 °C

Abstract: Aqueous sodium‐ion batteries (ASIBs) have attracted increasing attention for next‐generation energy storage technologies due to their abundant resources and environmentally‐safe, while their application scenarios are severely limited by the high freezing point of conventional aqueous electrolytes. To overcome the aforementioned issues of ASIBs, a novel hybrid 3.5 m Mg(ClO4)2+0.5 m NaClO4 electrolyte (m: mol kg−1) with an ultra‐low freezing point (<−80 °C) is proposed. The exceptional anti‐freezing feature is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
0
17
0
3
Order By: Relevance
“…Reproduced with permission. [50] Copyright 2022, Wiley-VCH. e) 1 H NMR results for various electrolytes.…”
Section: Solute Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission. [50] Copyright 2022, Wiley-VCH. e) 1 H NMR results for various electrolytes.…”
Section: Solute Modificationmentioning
confidence: 99%
“…For instance, inorganic salt CaCl 2 and Mg(ClO 4 ) 2 were respectively added into the dilute NaClO 4 electrolyte in our previous work to prepare hybrid electrolytes. [9,50] Experiment results demonstrated that both the optimized 3.86 m CaCl 2 + 1 m NaClO 4 electrolyte and 3.5 m Mg(ClO 4 ) 2 + 0.5 m NaClO 4 electrolyte had ultra-low freezing points of <−50 and <−80 °C (Figure 2d), respectively. Compared with the control sample of 1 m NaClO 4 electrolyte, the 1 H nuclear magnetic resonance (NMR) peak in the 3.86 m CaCl 2 + 1 m NaClO 4 electrolyte shifted lower frequency, revealing that Ca 2+ had an more apparent influence on modulating the chemical environment of water molecules (Figure 2e).…”
Section: Solute Modificationmentioning
confidence: 99%
“…随着全球对可持续发展战略的重视, 能够将清洁的可再生能源转化并储存起 来的储能技术越来越重要 [1,2] 。锂离子电池的商业化发展取得了巨大的成功,但 易燃的有机电解质存在潜在的安全隐患,亟需开发新型的储能技术 [3,4] 。水系碱 金属离子电池由于具有不可燃、成本低,环境友好和离子电导率高等优势,成为 规模储能的候选技术之一 [5,6] 。自 2015 年 Suo 等人 [7] 提出 "盐包水" ( "Water-in-salt") 的策略以来, 极大扩宽了水系电解液的电化学窗口并提升了水系电池的能量密度, 为水系碱金属电池的进一步发展带来了曙光。在水系碱金属离子电池中,水系锂 离子电池是发展最早且研究最为丰富的一种,相比之下,水系钠离子和钾离子电 池的研究起步较晚,但其电化学反应机理与水系锂离子电池类似,且钠元素和钾 元素在地球中的储量极为丰富,因此成为近几年的热点研究方向 [8] 。 随着近年来对储能技术需求的多元化, 越来越多的电池或将在极端天气环境 下应用,尤其是寒冷天气和高纬度地区 [9,10] 。开发在低温下仍可保持优异电化学 性能的水系碱金属离子电池变得尤为重要。目前,水系碱金属离子电池在低温下 面临的主要问题是: (1)由于热力学限制,水在 0℃以下会结冰。虽然溶质的加 入可降低电解液的凝固点,但在低温下电解液的粘度增加,离子电导率降低,减 缓了离子在电解液中的传输; (2)电极在低温下离子扩散速率缓慢,嵌入/脱出 动力学较差,引起较大极化,使电极容量释放不充分; (3)低温下电解液对电极 的浸润性变差,界面阻抗增大使电池运行困难。 针对水系碱金属离子电池在低温条件下面临的上述问题问题, 研究学者提出 了不同的解决方案: (1)通过增加盐浓度 [11][12][13] 、加入添加剂/共溶剂 [14][15][16] 、引入 水凝胶 [17,18] 来降低电解液的凝固点; (2)通过调控电极的结构和形貌改善材料的 离子扩散速率 [19,20] ,或使用有机电极 [13,[21][22][23] -Zn 电极 [24,25] 等非嵌入/脱出型电极减 缓低温下载流子的去溶剂化过程或采用双离子电池机制缩短电池反应路径 [26,27] ; (3)引入可在电极表面生成保护层的有机溶剂 [28] 制了分子和离子的热力学运动,导致电池无法运行 [29,30] 。通过使用高浓度或饱和 电解液 [11][12][13] ,可增强电解液中离子与水分子间的相互作用,抑制水分子间氢键的 形成,降低电解液的凝固点,从而提高水系碱金属离子电池的低温性能。然而高 浓度或饱和电解液接近盐的溶解极限,在低温下极易析出引发电池故障。2019 年,Battaglia 等人 [31]…”
Section: 引 言unclassified
“…外,其余砜类 [33] ,醇类 [19] ,腈类 [34] ,糖类 [35] 等有机物溶液也均是常用的有机低 温添加剂。 此外, 在电解液中加入与水分子有强烈相互作用的无机盐也可降低电解液的 凝固点,含有卤素阴离子(Cl -,Br -等)或高氯酸根阴离子(ClO 4 -)和多价阳离子 (Zn 2+ ,Mg 2+ ,Ca 2+ 等)的无机盐是常见代表 [14,36] 。其中,低成本的 CaCl 2 与水分子 间有强烈的相互作用,从而可调节水分子间的氢键比例,是防冻剂的常见成分。 2022 年,南开大学的焦丽芳课题组报道了 3.86 m CaCl 2 + 1 m NaClO 4 的新型电 解液 [36] ,如图 2 (h) ,该电解液可使 Na 2 CoFe(CN) 6 //AC 全电池在-30℃运行且容 量保持为的室温容量的 64.8%。 将上述策略与水凝胶相结合往往可以得到拥有高耐用性的柔性低温水系碱 金属离子电池。苏州大学的严锋课题组 [18] ;(c) LiPTFSI、LiOTf 及其二元混合物的水溶液的相图 [32] ;(d) 水/DMSO ( χ DMSO =0.30) 混合物的 DSC 曲线(在水溶液中加入摩尔分数为 0.3 的 DMSO) [15] ;(e)-(g) 三种全电池在 25℃和-50℃的充放电曲线 [15] ; (h) Na 2 CoFe(CN) 6 //AC 全电池在 25℃和-30℃下的充放电曲线 [36] ;(i) LTP@C //PIL-OH 水凝胶//AC 全电池在不同温度下的充放电曲线 [18] ;(j) 全电池连 续在不同温度下循环的容量变化 [18] LiFSI+10 m LiTFSI) between 60 and -120℃ [31] ; (b) the optical photographs of 25 m LiFSI+10 m LiFTFSI and 25 m LiFSI+10 m LiTFSI after storage at 0℃ for 4 weeks [31] ; (c) the phase diagrams of aqueous solutions of LiPTFSI, LiOTf, and their binary mixtures [32] ; (d) the DSC result of χ DMSO =0.3 electrolyte solvent [15] ; (e)-(g) GCD curves of different batteries at 25℃ and -50℃ [15] ; (h) the GCD curves of the Na 2 CoFe(CN) 6 //AC full cells at 25℃ and -30℃ for different cycles [36] ;…”
Section: 引 言unclassified
See 1 more Smart Citation